Pelatihan Pengolahan Abon Jamur Tiram Pada Masyarakat Jati Mulyo Kecamatan Dendang Kabupaten Tanjung Jabung Timur - Safitri, Deslina; Adawiyah, Robiatul; Hasidqy, M. Hasby; Minarni (Journal of Community Engagement Research for Sustainability, 2023)
White oyster mushrooms (Pleurotus Ostreatus) are a type of edible mushroom that is quite popular with the public and is for the body because it is highly nutritious and low in fat. A few days after harvest, the quality of oyster mushrooms until they are unfit for consumption. Changes in the quality of oyster mushrooms include wilting, the color turning brown, soft taste changing, where to maintain of oyster mushrooms there is innovation processed food products. This community service activity is a form of parties make processed food from increase economic value. The target of this service PKK women of Jati Mulyo Village, for the reason this village we carried Oyster Mushroom Breeding using Empty Oil Palm Bunches (TKKS) using baglog as a growing medium for oyster mushrooms. This activity oyster mushroom processed product into shredded oyster mushrooms, they become a food product that durable, easy to consume, and has high selling value.